Successful transportation of wild stock of endangered "Thooli" (Labeo dussumieri) spawners without anaesthetics - Gopalakrishnan, A; Ponniah, A G; Basheer, V S; Padmakumar, K G; Krishnan, Anuradha; Lal, Kuldeep K (Indian Journal of Fisheries, 2011)
Several problems are encountered during transportation of fishes from wild tocaptivity. The note describes successful transportation of wild caught endangeredLabeo dussumieri spawners over distances below 100 km without anesthesia orsophisticated transporting devices which is of immense help in the gene bankingprogramme of endangered species